In Silico Drug Design of Sembukan (Paederia scandenz) As Anti-Breast Cancer Agents - Eva Ulfiatus Shofia; R. Susanti (Universitas Negeri Semarang, 2025)
cancer is a disease of excessive cell growth and is one of the cases of disease that has increased every year. cancer treatment therapy in the form of chemotherapy drugs has various side effects so that safer long-term treatment is needed, namely using herbal medicines such as sembukan plants (Paederia scandens). This research was conducted using experimental methods computationally through in silico methods as a potential prediction test as a reference for further studies. isolate compounds are carried out molecular tethering against progesterone, estrogen, HER2, and NfkB receptors using PyRx 0.8 software. Then the isolated compounds were tested for the feasibility of chemical and pharmacokinetic properties and toxicity using the Lipinski Rules of Five data base and ADMETLab 3.0. Furthermore, visualization was carried out to see the bonding interaction between ligand and receptor protein using Biovia Discovery Studio 2024 software. Based on the results of molecular tethering compounds Kaempferol 3-rutinoside-7-glucoside, Cosmetin, Quercetin 3-o-rutinoside-7-o-glucoside, Daidzein and Linarin have the potential as inhibitors respectively against progesterone, HER2, Nf-kB, estrogen and overall average receptors with each binding affinity value of -9. 6 kcal/mol, -9.8 kcal/mol, -9.8 kcal/mol, -10.8 kcal/mol, -8.9 kcal/mol and -9.0 kcal/mol respectively. The best physico-chemical properties were obtained for Daidzein and Linarin compounds. Visualization data generated that Kaempferol 3-rutinoside-7-glucoside, Cosmetin, Quercetin 3-o-rutinoside-7-o-glucoside, Daidzein and Linarin compounds have similar interactions and amino acid residues with control drugs so that they are predicted to have similar pharmacological effects as breast anticancer.